Chest pain in children and adolescents - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2010)
Chest pain is a common complaint which is usually related to non-cardiac causes in children and adolescents. Musculoskeletal system, lungs, gastrointestinal system, heart, psychiatric causes may be the source of the pain. Long lasting, recurrent, sharp pain which is not related with exercise is usually benign and the cause of the pain can not be found in some patients. These are called as idiopathic chest pain. Despite the rarity of cardiac causes, exclusion of cardiac disease is important in the differential diagnosis since they can lead to mortality and morbidity. Cardiac chest pain must be considered in patients with exercise related, burning or squeezing pain over the sternum which can radiate towards the left arm or neck. Positive family history, accompanying symptoms such as syncope, palpitation, decreased exercise capacity, abnormal physical or electrocardiographic findings are indications for detailed cardiac investigation. (Turk Arch Ped 2010; 45: 2-5)
Keywords: Chest pain; electrocardiogram; sudden death